I-firewall: dynamic linux firewall rule update using ansible / Tengku Muhammad Faris Tengku Abdul Halim - Tengku Abdul Halim, Tengku Muhammad Faris (2021)
Nowadays, the cyber-attack case has increasing rapidly in our world as our culture of using the network as the network become our needed in our daily life. So, in order to mitigate the attack from intrude into our network, network security is needed in this case such as Firewall. Firewall is a system design to prevent unauthorized access to or from a private network. Nowadays, the network threat is dynamic and rapidly changing, thus we need a mechanism to dynamically update the firewall rules without hassle. I-Firewall: Dynamic Linux Firewall’s Rule Update Using Ansible will be run in VMware as the platform. This security system will be develop using Python programming language and used in a Linux OS. This system will be develop using the automation tools which is Ansible that is function as the update rule’s firewall and monitoring server. From this project, the security of the network will be more secure as it uses automatic update rule if new threat is detected. This project will be focus more on the home network user only. This project aims are to develop a security that is more secure for the network using this I-Firewall.